РАЦИОНАЛЬНОЕ ПРИРОДОПОЛЬЗОВАНИЕ И УСТОЙЧИВОЕ РАЗВИТИЕ ЭКОНОМИКИ НА СОВРЕМЕННОМ ЭТАПЕ (Journal of Economic Research & Business Administration, 2015)
In this article ekologo-economic problems of agriculture taking into account a qualitative irrigation of agricultural grounds in Republic Kazakhstan are considered. An irrigation pesticides of better продукций approved for the population the certificate of the goods of quality.